INCLUSIVE EDUCATION IN TEACHER TRAINING: REFLECTIONS ON THE CURRICULAR MATRIX OF THE BACHELOR’S DEGREE IN GEOGRAPHY AT IFMG – OURO PRETO (REMUNOM, 2025)
This study analyzes the approach to Inclusive Education in the Bachelor's Degree in Geography at the Federal Institute of Minas Gerais (IFMG), Ouro Preto campus. The research investigates how the curricular matrix and the Course Pedagogical Project (PPC) address teacher training for inclusion, highlighting courses such as Brazilian Sign Language (LIBRAS) and Curriculum, Diversity, Gender, and Race. The qualitative research was divided into three stages: literature review, analysis of data on the inclusion of students with disabilities in basic education, and analysis of the course’s curricular matrix. The results indicate the presence of few compulsory courses directly addressing Inclusive Education, which limits a comprehensive training of future teachers. The inclusion of more courses is suggested to enrich teacher training, ensuring that teachers are better prepared to address the diversity present in classrooms. The study also discusses the importance of increasing the workload of inclusion-related courses, considering the complexity of the subject and the need for teaching that truly meets the needs of all students, regardless of their conditions.